2014
DOI: 10.1111/ssqu.12116
|View full text |Cite
|
Sign up to set email alerts
|

Young Voters and War: The Iraq War as a Catalyst for Political Participation

Abstract: Objective We investigate whether the Iraq War might be a catalyzing event for this generation, like Vietnam was for baby boomers or World War II for the “greatest generation,” through testing how opinions about the war influence patterns of political participation. Methods Using data from an Internet‐based survey of randomly sampled college students at a midwestern state university and the 2008 National Election Studies, we investigate the relationship between disapproval of Bush's handling of the Iraq War and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Students who opposed the Bush administration’s handling of the war should have been more energized to participate politically because the election offered the potential for bringing policy change. Moffett, Rice, and Madupalli (in press) discovered that college students who opposed Bush’s handling of the Iraq war are more civically engaged, and Best and Krueger (2005) found that those who participate online are more likely to oppose the war in Iraq. Consequently, we expect that students who oppose the war will be more civically engaged than those who support it.…”
Section: Political Characteristicsmentioning
confidence: 99%
“…Students who opposed the Bush administration’s handling of the war should have been more energized to participate politically because the election offered the potential for bringing policy change. Moffett, Rice, and Madupalli (in press) discovered that college students who opposed Bush’s handling of the Iraq war are more civically engaged, and Best and Krueger (2005) found that those who participate online are more likely to oppose the war in Iraq. Consequently, we expect that students who oppose the war will be more civically engaged than those who support it.…”
Section: Political Characteristicsmentioning
confidence: 99%